A brief comparison of Vietnamese intonation and English intonation and its implications for teaching English intonation to Vietnamese EFL learners - Nhung, Luu Thi Kim (VNU Journal of Foreign Studies; Vol 26 No 3, 2010)
Abstract. Intonation is important for learners of English because even with satisfactory consonants and vowels, a phrase/sentence with an incorrect intonation contour may change the intended meaning of the whole utterance. This study, basing its observation and formulation on earlier publications, will briefly compare Vietnamese intonation and English intonation as well as highlight some problems Vietnamese speakers are likely to have in learning English intonation due to the differences between these two language intonations, and to offer some implications for teaching English intonation to Vietnamese EFL learners.